Задача о построении математической модели динамического хеджирования - Гаращенко, Ф.Г.; Солошенко, Ю.И.; Кулян, В.Г. (Кибернетика и вычислительная техника, 2012)
Рассматривается задача построения математической модели динамического хеджирования проданного опциона колл на корзину акций с учетом транзакционных издержек. Исследована динамика стоимости инвестиционного портфеля при транзакционных затратах. Сформулирована задача управления динамическим хеджированием портфеля. Розглянуто задачу побудови математичної моделі динамічного хеджування проданого опціону колл на корзину акцій з урахуванням транзакційних витрат. Вивчено динаміку вартості інвестиційного портфеля при транзакційних витратах. Сформульовано задачу керування динамічним хеджуванням портфеля. In this paper we develop a mathematical model to the problem of dynamic hedging of European basket call options. Proportional transaction costs are included to the model, to make this model more applicable to solving practical tasks. Also we used standard models for underlying stock dynamics as a starting point for researches. The hedging problem for a European call option is formulated as a finite horizon constrained stochastic control problem. We used first and second moments in our criterion formulation, to achieve fast computations. Also in model two assumptions are used. In first we assume that initial capital is given. In the second we assume that we do not have positions in underlying stocks at the start and after the end of our time period. This assumption was made due to type of estimations for option contracts in Ukraine. Developed mathematical model allows making practical experiments in solving the dynamic hedging of sold call option on a basket of assets.